50 bp deletion in promoter superoxide dismutase 1 gene and increasing risk of cardiovascular disease in Mashhad stroke and heart atherosclerotic disorder cohort study. (31st October 2019) - Darroudi, Susan; Tajbakhsh, Amir; Esmaily, Habibollah; Ghazizadeh, Hamideh; Zamani, Parvin; Sadabadi, Fatemeh; Tayefi, Maryam; Tayefi, Batool; Fereydouni, Narges; Mouhebati, Mohsen; Akbari Sark, Noushin; Avan, Amir; et al.
Abstract: Cardiovascular disease (CVD), one of the main mortality causes worldwide is considered to be affected by general oxidative stress and inadequacy antioxidant system. Superoxide dismutase 1 (SOD1), a cytosolic antioxidant enzyme has a key role in neutralizing the excessive prooxidant by scavenging the super oxide anions. SOD1 polymorphic variants exhibit the altered activity properties. In the current study, we are aimed to investigate the association between the SOD1 polymorphism and CVD prevalence. A 6‐years case control follow up study was designed to genotype the 526 participants (311 controls and 215 cases) for studying the 50 bp INS/DEL polymorphism at SOD1 promoter gene and analyze their blood lipid profile and anthropometric characteristics. Among the two possible alleles of the SOD1 gene (Wild [W] and Mutant [M]) the meaningful association was detected between the Mutants' frequency and the prevalence of CVD patients ( p ‐value <.001). The W and M allele refer to inserted and deleted 50 bp in the polymorphic site of the SOD1 promoter, respectively. The WM and MM genotypes' frequency which indicate the wild heterozygotes and Mutant homozygotes, respectively, were significantly correlated with the prevalence of cardiovascular disease ( p ‐value <.001). The present study has the potential to introduce the 50 bp INS/DEL polymorphism of SOD1 genotyping as a novel unique diagnostic approach for screening the high risk CVD.